The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/2017jd027316
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Isocyanate, Amide, Nitrate, and Nitro Compounds From an Anthropogenic Biomass Burning Event Using a ToF‐CIMS

Abstract: Anthropogenic biomass burning is poorly represented in models due to a lack of observational data but represents a significant source of short‐lived toxic gases. Guy Fawkes Night (bonfire night) is a regular UK‐wide event where open fires are lit and fireworks are set off on 5 November. Previous gas phase studies of bonfire night focus on persistent organic pollutants primarily using off‐line techniques. Here the first simultaneous online gas phase measurements of several classes of compounds including isocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 99 publications
5
53
0
Order By: Relevance
“…19 This result is consistent with measurements made during a nationwide bonre event in the UK where HNCO/CO ratios were observed to be 3 times higher during a period when emissions were thought to be dominated by aming combustion compared to smouldering. 58 In addition, this Guy Fawkes Night study found that plumes associated with bonres had maximum mixing ratios of 1.64 ppbv HNCO, a two-order of magnitude enhancement of the mean non-bonre mixing ratio of 0.012 ppbv. 58 Different parameters such as protein content and temperature determine how much HNCO is released during biomass burning.…”
Section: Biomass Burningmentioning
confidence: 91%
See 1 more Smart Citation
“…19 This result is consistent with measurements made during a nationwide bonre event in the UK where HNCO/CO ratios were observed to be 3 times higher during a period when emissions were thought to be dominated by aming combustion compared to smouldering. 58 In addition, this Guy Fawkes Night study found that plumes associated with bonres had maximum mixing ratios of 1.64 ppbv HNCO, a two-order of magnitude enhancement of the mean non-bonre mixing ratio of 0.012 ppbv. 58 Different parameters such as protein content and temperature determine how much HNCO is released during biomass burning.…”
Section: Biomass Burningmentioning
confidence: 91%
“…60 In the Fort Collins and Manchester data sets, there is an early morning minimum with increasing concentrations throughout the day to a late aernoon maximum. 26,58 One hypothesis for the late aernoon peak observed in some datasets is the production of HNCO through secondary photochemical sources. 26 Support for secondary production comes from two lines of evidence.…”
Section: Ambient Measurementsmentioning
confidence: 99%
“…The I-CIMS is sensitive to acids and multifunctional oxygenates (Lee et al, 2014), which are likely to form as secondary NMOGs in biomass burning plumes. I-CIMS has been used to evaluate primary NMOG emissions (e.g., Priestley et al, 2018;Reyes-Villegas et al, 2018;Tomaz et al, 2018), biomass burning emissions aged by nocturnal processes (Ahern et al, 2018;Reyes-Villegas et al, 2018), and primary particle-phase components (Gaston et al, 2016). I-CIMS spectra of the NMOGs resulting from the OH oxidation of biomass burning smoke have yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The UoM-CIMS setup has been described elsewhere (Priestley et al, 2018); a Filter Inlet for Gases and AEROsols (FI-GAERO; Lopez-Hilfiker et al, 2014) was additionally used in this study. The gas-phase inlet of UoM-CIMS consisted of 5 m 1/4 ID PFA tubing connected to a fast inlet pump with a total flow rate of 13 SLM from which the ToF-CIMS sub-sampled 2 SLM.…”
Section: Uom-cimsmentioning
confidence: 99%